ESTIMASI VARIANSI PADA PENARIKAN SAMPEL DUA TAHAP UNTUK DATA TIDAK LENGKAP - Subanti, Sri (MATEMATIKA, 2003)
Rasio estimation under two – phase simple random sampling is studied. A new linearisation variance estimator that makes more complete use of the sample data than a standard one is proposed. A jackknife variance estimator and its linearised version are also obtained. Unconditional and conditional repeated sampling properties of these variance estimaters are studied through simulation. Applications to ‘mass’ imputation under two – phase sampling and deterministie imputation for missing data are also given.